Methodological strategies applied by teachers to develop the interest and learning of students in the english class - Torres Castillo, Andrea Mabel (Machala: Universidad Tecnica de Machala, 2016)
This project focuses on the application of different methodological strategies that help teachers to develop interest and learning of students in english class. these strategies are very important in the english classroom because for students the subject of english is tedious and difficult to learn. the objective of this document is to provide teachers methodological strategies through innovative and motivating techniques to achieve quality and active teaching-learning. it is vital in the classroom, the management and use of the proposed strategies that help students to interact and build their own knowledge. this research provides support to teachers to guide how to teach a class to motivate their students, and they achieve good learning by developing the four skills: reading, speaking, writing, listening.
Keywords: STRATEGY; MOTIVATION; TECHNIQUE; LEARNING; INTEREST